2016
DOI: 10.1111/apha.12700
|View full text |Cite
|
Sign up to set email alerts
|

PAFAH1B1 and the lncRNA NONHSAT073641 maintain an angiogenic phenotype in human endothelial cells

Abstract: PAFAH1B1 and NONHSAT073641 are important for endothelial angiogenic function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 51 publications
0
11
1
Order By: Relevance
“…Quantification of 20-HETE was done in principle as described previously 66 . In brief, 200 μl supernatant were spiked with the corresponding deuterated internal standards and extracted by liquid–liquid extraction using ethyl acetate.…”
Section: Methodsmentioning
confidence: 99%
“…Quantification of 20-HETE was done in principle as described previously 66 . In brief, 200 μl supernatant were spiked with the corresponding deuterated internal standards and extracted by liquid–liquid extraction using ethyl acetate.…”
Section: Methodsmentioning
confidence: 99%
“…LncRNA AK094457 was shown to enhance iNOS and nitric oxide (NO) expression in vascular ECs, suggesting a potential role in regulating blood pressure 132 . In an independent study, LncRNA NONHSAT073641 is upregulated in lung tissues from subjects with chronic thromboembolic pulmonary hypertension (CTEPH) and pulmonary veno-occlusive disease (PVOD) 133 . This lncRNA is highly homologous to the protein-coding gene, platelet-activating factor acetyl hybrdolase (PAFAH1B1).…”
Section: Lncrnas In Vascular Diseasementioning
confidence: 99%
“…Our previous studies have found there are 1614 differential mRNA genes (Fold change > 1.2 and P-value < 0.05), 185 lncRNAs (Fold change > 1.2 and P-value < 0.05) and 25 miRNAs (Fold change > 2 and P-value < 0.05) between the experimental and the control group. [11][12][13] Target genes predicted by miRNA and intersective genes 1: The number of target genes of 25 miRNAs predicted by miRanda is 10301. We intersected these genes with the 1614 differential mRNA genes from the microar-WANG, ET AL Figure 1.…”
Section: Microarray Analysis Outcomesmentioning
confidence: 99%
“…Another study demonstrated that lncRNA ENSG 00000262454 correlated with pericyte markers in idiopathic pulmonary arterial hypertension. 10) In the case of CTEPH, Josipovic, et al 11) found that lncRNA NONHSAT 073641 was upregulated in the vascular samples of pa-miRNA-genes-lncRNA NETWORK IN CTEPH tients with CTEPH and were important for endothelial angiogenic function. Competing endogenous RNAs (ceRNA) was found to lead to the hypothesis that lncRNA could interact with the gene through microRNA (miRNA) by competing for endogenous inhibition.…”
mentioning
confidence: 99%